Study Of Tobacco Chewing and Smoking Pattern and Its Socio-Demographic Determinants in A Tribal Village in Mandla District, Madhya Pradesh - Tomar, Shashi P; Kasar, Pradeep; Tiwari, Rajesh; Rajpoot, Surjeet; Nayak, Shubhangi (National Journal of Community Medicine, 2016)
Introduction: Tobacco chewing and smoking are considered serious public health problems in many countries including India because of the associated health hazards hence this study done to know the extent and pattern of tobacco and smoking use and its socio-demographic variables in rural tribal village. Material and methods: A community based cross-sectional study was carried out in a tribal village, during the month of October14 to January 15 in 4month duration. 214 persons were interviewed by house to house visits with a pre-tested oral questionnaire method. Data were entered in excel and analyzed by SPS-14. Results: Tobacco chewing was slightly more among females (37.4%) as compared to males (34%) while it was just opposite for smoking none of the female in the village reported smoking while it was 5% among males. Mean age for initiation of tobacco chewing was 11.5±56SD for males and for females 9.6±79SD and and for smoking mean age of initiation among males was 16.7. Most common form consumed was tobacco followed by Pan Supari tobacco. Conclusion: In rural areas especially in tribal villages people are very much addicted to tobacco chewing so there is need to conduct effective interventions to control tobacco use.